CERMAT BERBAHASA INDONESIA SEBAGAI UPAYA MENINGKATKAN MUTU PENGGUNA BAHASA INDONESIA - Wahyono, Hari . (Majalah Transformatika, 2010)
Language is a tool Communication. Language has an important role as a. tool of communication. It is impossible for us to communicate without language.